Improved Student Learning Outcomes in Estimating the Total Price of Goods Using the Kahoot Application for Grade 2 Elementary School Students - Erma Dhamayanti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve student learning outcomes in estimating the total price of goods through the kahoot application. This research is a classroom action research conducted in three cycles. Each cycle consists of four stages, namely planning, implementing, observing, and reflecting. The research was conducted on the second grade students of SD Negeri Margasari 07 with a total of 20 students. This research was conducted at SD Negeri Margasari 07, Margasari District, Tegal Regency. When the study was conducted from October to November 2020. The results showed that student learning outcomes in estimating the total price of goods had increased. This can be seen from the average value of learning outcomes in the first cycle of 74 up to 80 in the second cycle. And in the third cycle the average value rose to 85. The number of students who completed the first cycle was 70%, in the second cycle it increased to 85% and in the third cycle it became 95%. So it can be concluded that using the Kahoot application can improve the learning outcomes of grade II SD Negeri Margasar 07 in estimating the total price of goods.